THE INFLUENCE OF CLOTHING ONLINE MARKETING ON PURCHASE DECISIONS IN ONLINE SHOPEE APPLICATIONS IN STUDENTS OF TRISAKTI TOURISM INSTITUTE - Mimi Enggriani; Triana Rosalina Dewi; Faiza Rachim (Universitas Islam Lamongan, 2023)
This study aims to determine the effect of online clothing marketing on purchasing decisions in the Shopee online application for Trisakti Tourism Institute students. This type of research is descriptive quantitative with simple regression analysis method and sampling by random sampling. The number of samples is 100 0 people. The results of the study show that clothing online marketing has a significant effect on purchasing decisions in the Shopee online application. Online clothing marketing has a significant impact on the purchasing decisions of Trisakti Institute of Tourism students because of the ease of accessing online stores via mobile devices, providing a wider selection, promotions and discounts, product reviews and ratings, and the ability to easily share information with friends through social media.